Return of Vilnius territory and lost of Lithuanian independance - Jakubčionis, Algirdas (Genocidas ir rezistencija, 2003)
The international situation of Lithuania in 1939–1940 is described in simple terms: from ultimatum to ultimatum, and from ultimatum to the loss of independence. On 17 March 1938, Poland issued an ultimatum to Lithuania, setting a precedent for the acceptance of ultimatums. On 20 March 1939, Germany issued an ultimatum, resulting in the loss of part of the Lithuanian territory. On 14 June 1940, the Soviet Union issued an ultimatum depriving Lithuania of its statehood.